A Bibliometric Analysis of Aloe vera in Wound Healing - Asti Arum Sari; Reza Rahmawati (Universitas Muhammadiyah Surakarta, 2023)
People have used Aloe vera for a variety of traditional medical applications. A. vera has been proven in numerous studies to play a key function in wound healing. Although there are many reviews on this topic, bibliometric analysis is not found in the literature. This study uses bibliometric analysis to evaluate the influence and relevance of the countries, journals, organizations, and authors that have made the most contributions to this topic. Scopus database was used to gather bibliographic data on relevant studies. A total of 417 published articles between 1981 and 2023 were selected. VOSviewer version 1.6.18 was used to conduct a bibliometric analysis of these papers. On the topic of A. vera as a wound healing agent, Tehran University of Medical Science from Thailand was the most productive institution and Journal of Ethnopharmacology was the most productive journal. India was the most productive and collaborative country. The spotlight of the recent papers was the use of biotechnology techniques and drug-delivery strategies of A. vera in wound healing. Developing formulation using various drug-delivery methods followed by in vivo preclinical and clinical studies of this particular topic were potential to be explored.